Foot and ankle COVID-19 clinical manifestation: an integrative review - Hugo Morais Ruela, Victor; Silva Bochi, Gabriela; Souza Júnior, Eli Ávila (Journal of the Foot & Ankle, 2023)
Objective: Review the literature to obtain evidence of whether COVID-19 causes or exacerbates signs and symptoms in the foot and ankle. Methods: This is an integrative literature review. Articles from the Scielo and PubMed platforms, published between January 2020 and April 2023, were selected and obtained by combining the descriptors “COVID-19”, “Signs and Symptoms”, “Joints”, “Foot”, and “Ankle”, which answered the question guide: “What are the signs and symptoms in feet and ankles presented by patients affected by COVID-19?” Results: Twenty-one articles were included, and data related to COVID-19 manifestation in the feet and ankles were extracted. The findings were grouped into dermatological, neurological, vascular, and musculoskeletal manifestations. The most prevalent dermatological manifestation was a chilblain-like lesion. The vascular manifestations include arterial thrombosis, vasculitis, and subacute arterial ischemia. Regarding the neurological findings, mononeuropathies and polyneuropathies were cited, including paresthesia and paresis in the feet and deep ankle areflexia. Among the musculoskeletal findings are reactive arthritis (with arthralgia in the ankle and foot, Achilles tendon enthesitis, redness, and edema), dactylitis, and heterotopic ossification in the ankle. Conclusion: COVID-19 causes or exacerbates dermatological, neurological, vascular, and musculoskeletal signs and symptoms in the feet and ankles. Level of Evidence IV; Diagnostic Studies; Integrative review.